Photocatalytic Activity, Surface Morphology, and Mechanical Properties of Atmospheric Plasma-treated HTPET Fiber with SnO2 Coating (Journal of Fiber Bioengineering and Informatics, 2018)
SnO_2 hydrosol made in the lab was deposited on HTPET fibers by dip-coating method. In order toimprove the deposition of the coating layer and water adsorption properties of the fiber, atmosphericplasma treatment was used as pre-treatment to enhance the interaction at the interface. Photocatalyticproperties of the samples coated with SnO_2 under different plasma treatments were analyzed throughthe degradation of methylene blue under UV-light. The morphologies and surface modulus of SnO_2coated fibers were characterized by Scanning Electronic Microscope (SEM) and Atomic Force Microscopy(AFM), respectively. The effects of plasma treatment on water adsorption behavior of the fibers wereexamined by contact angle measurement instrument. Tensile tests were carried out to measure and assessthe mechanical properties of HTPET fiber before and after plasma treatment and photocatalysis wasdone. The study revealed that the photocatalytic activity of SnO_2 coated HTPET fibers were enhanceddue to the wettability of HTPET surfaces improved by plasma treatment and varying degrees of surfaceetching which benefited SnO_2 adhesion on HTPET fibers. Meanwhile, the modulus of monofilamentsurface increased under plasma treatment but decreased after phtotcatalysis. Mechanical properties ofthe fibers exhibited an opposite trend. It was found that the best photocatalytic activity of HTPETfibre was obtained under 100 w power plasma treatment.